Antigen recognition and IL-2 receptor gene expression as evidence against clonal deletion in mice with neonatally induced transplantation tolerance - Holán, V; Lipoldová, M (Cellular immunology, 1992)
Neonatal transplantation tolerance was induced in B10.A mice by the injection of spleen and bone marrow cells from semiallogeneic [C57BL/10(B10) x B10.A] F1 donors. The neonatally treated mice accepted skin grafts from B10 donors. Spleen cells from tolerant animals did not respond by proliferation to tolerated B10 antigens in vitro. However, spleen cells from tolerant mice recognized specific (B10) antigens and synthesized mRNA for the inducible 55-kDa interleukin-2 receptor (IL-2R) as did cells from normal animals. Maintenance of this early phase of cell activation upon contact with tolerated antigens is direct evidence against clonal deletion as a mechanism, in this particular model of neonatally induced transplantation tolerance.
Keywords: messenger RNA; Animals, Newborn; imunologická tolerance; Transplantation Immunology; myši inbrední C57BL; Receptors, Interleukin-2; Mice; histokompatibilní antigeny; novorozená zvířata; transplantační imunologie; buňky kostní dřeně; slezina; Models, Biological; Gene Expression; RNA, Messenger; zvířata; Bone Marrow Cells; biologické modely; myši; Immune Tolerance; exprese genu; Spleen; receptory interleukinu-2; Mice, Inbred C57BL; Histocompatibility Antigens; Animals